PENGARUH INFLASI DAN TINGKAT SUKU BUNGA TERHADAP PROFITABILITAS PADA PT PANIN FINANCIAL TBK PERIODE 2013-2022 - Pratiwi, Intan; Nurwita (Journal of Research and Publication Innovation, 2024)
This research aims to determine the effect of inflation and interest rates on profitability partially or simultaneously at the panin financial company for the 2013-2022 period. The research method used is a quantitative descriptive research method. This research uses secondary data, namely data that is already available or that has been processed by other parties and published. This research data was obtained through the website www.bi.go.id for collecting inflation data and BI rate and panin financial’s financial reports obtained through www.paninfinancial.co.id. The tool used for testing is the normality test which includes the normality test, multicollinearity test, heteroscedasticity test, and autocorrelation test. Apart from that, multiple linear regression tests, coefficient of determination tests, and finally partial (individual) and simultaneous (together) hypothesis tests are also used. The results of research based on the T or partial test using SPSS 20 show that the inflation variable has a tcount value of 1.471 with a ttable value of 2.365, which means tcount < ttable, and a significance value of 0.185 > 0.05 which can be concluded that inflation has no significant effect on profitability (ROA). Partially, the interest rate variable on profitability (ROA) has a tcount value of 0.185 with a ttable value of 2.365 and a significance value of 0.858 > 0.05, which means it has no effect. Simultaneously, inflation and interest rates together have an Fcount value of 1.775 and an Ftable of 4.74, so 1.775 < 4.74 and a significance value of 0.238 > 0.05, so it can be said that there is no significant effect with an R square value of 0.337 or 33,7%.